POTENSI EKSTRAK ETANOL LABU SIAM (Sechium edule) UNTUK PERBAIKAN KERUSAKAN SEL BETA PANKREAS DAN KADAR NITROGEN OKSIDA PADA TIKUS YANG MENGALAMI DIABETES MELITUS (The Potenty of Sechium edule Ethanolic Extract to Repair Beta Pancreas Cells and Nitrogen Oxide Concentration in Streptozotocin-induced Diabetic Rat) - Lukiati, Betty; Maslikah, Siti Imroatul; N, Nugrahaningsih (Jurnal Kedokteran Hewan, 2016)
The objectives of this research were to examine the effect of Sechium edule ethanolic extract to repair beta pancreas cells damage and tomeasure nitrogen oxide (NO) concentration in streptozotocin-induced rats. Type I diabetic rats were obtained by intraperioneally injected therats with multiple low dose streptozotocin (MLD-STZ) for 5 days. In this research, rats were assigned into 5 treatment groups: untreated rats ingroup 1 were considered as negative control, while MLD-STZ induced type 1 diabetic rats in group 2 were considered as positive control. Inanother 3 groups, type 1 diabetic rats were orally treated with three doses of Sechium edule ethanolic extract (14, 28, 42 mg/kg bw) respectivelyfor 7 consecutive days. Repairing of beta pancreas cells were analyzed descriptively whereas concentration of NO were analyzed using one wayANOVA and continued with LSD test (= 0.01). The result showed that the administration of Sechium edule ethanolic extract significantlydecreased NO concentration (P0.01) up to 67.9 M and repaired beta pancreas cells damage. Dose of 42 mg/kg bw of Sechium edule ethanolicextract is the effective dose for diabetic rat therapy. Key words: Sechium edule extract, diabetic mellitus, rat, beta pancreas cells